Banks, Low Interest Rates, and Monetary Policy Transmission - WANG, OLIVIER (Journal of Finance, 2025)
ABSTRACT I study how the secular decline in interest rates affects banks' intermediation spreads and credit supply. Following a permanent decrease in rates, bank lending may rise initially but contracts in the long run. As lower rates compress deposit spreads even well above the zero lower bound, banks' retained earnings, equity, and lending fall until loan spreads have risen enough to offset the reduction in deposit spreads. A higher inflation target can support bank lending at the cost of higher liquidity premia. I find support for the model's predictions in U.S. aggregate and bank‐level data.